2018
DOI: 10.1186/s13014-018-1129-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of response to preoperative radiotherapy in locally advanced breast cancer

Abstract: BackgroundRadiation therapy is an indispensable part of various treatment modalities for breast cancer. Specifically, for non-inflammatory locally advanced breast cancer (LABC) patients, preoperative radiotherapy (pRT) is currently indicated as a second line therapy in the event of lack of response to neoadjuvant chemotherapy. Still approximately one third of patients fails to respond favourably to pRT. The aim of this study was to explore molecular mechanisms underlying differential response to radiotherapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Only one study that correlates MMPs and TIMPs with RT was found on the GEO database (GSE101920). 34 This study shows the gene expression profile in BC biopsies taken both prior to RT, and after RT and radical mastectomy. Due to the limited number of matched samples (n = 5) obtained, the study was continued by focusing on the analysis of pre-RT biopsies only.…”
Section: Geo Databasementioning
confidence: 92%
“…Only one study that correlates MMPs and TIMPs with RT was found on the GEO database (GSE101920). 34 This study shows the gene expression profile in BC biopsies taken both prior to RT, and after RT and radical mastectomy. Due to the limited number of matched samples (n = 5) obtained, the study was continued by focusing on the analysis of pre-RT biopsies only.…”
Section: Geo Databasementioning
confidence: 92%
“…The standard treatment of locally advanced breast cancer (LABC) is almost always multimodal and involves systemic therapy with chemotherapy (CT) and/or hormone therapy (HT), surgery and RT 4 5. Systemic therapy is usually the first approach, however, more than a third of patients may not respond as expected 6 7. When inoperability criteria prevails, RT should be used for tumour downstaging.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have generated an RSS base on the intrinsic radiosensitivity in BRCA by the integration of post-radiation clonogenic survival data with gene expression data [11,[24][25][26]. To demonstrate whether immune infiltration level has predictive ability for RT outcomes, we developed a Radiosensitivity Signature (RSS) in BRCA ( Figure 5).…”
Section: Brca Radiosensitivity Signature Based On Immune Infiltrationmentioning
confidence: 99%
“…Finally, Gene Ontology (GO) analyses were employed to define key molecular biomarkers governing response to radiation in rectal cancer [9]. However, all these studies were based on the intrinsic radiation response of tumor cells and the effects of the TME on this response were ignored [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation